Safety-First and Expected Utility Maximization in Mean-Standard Deviation Portfolio Analysis - Pyle, David H.; Turnovsky, Stephen J. (The Review of Economics and Statistics, 1970)
David H. Pyle, Stephen J. Turnovsky, Safety-First and Expected Utility Maximization in Mean-Standard Deviation Portfolio Analysis, The Review of Economics and Statistics, Vol. 52, No. 1 (Feb., 1970), pp. 75-81